Improving Operating Time for External Laser Source based Polymer Fiber by Optimizing Model Parameters - Hisham, Hisham Kadhum; Marzook, Ali Kamel (Iraqi Journal for Electrical and Electronic Engineering, 2024)
In this paper, an analysis of performance acceleration of an external laser source (ELS) model based polymer fiber gratings (PFGs) by reducing the turn-on delay time (TDelay) is successfully investigated numerically by optimizing model parameters. In contrast to all previous studies that relied either on approximate or experimental equations, the analysis was based on an exact numerical formula. The analysis is based on the investigation of the effect of diode injected current (Iin j), temperature (T), recombination rate coefficients (i.e. Anr, B, and C), and optical feedback (OFB) level. Results have demonstrated that by optimizing model parameters the Delay can be controlled and reduced effectively.